2009
DOI: 10.14214/sf.171
|View full text |Cite
|
Sign up to set email alerts
|

Snag abundance and species composition in a managed forest landscape in central Japan composed of Larix kaempferi plantations and secondary broadleaf forests

Abstract: Larix kaempferi is the main plantation species in the low-snow, cool-temperate zone of Japan. I studied L. kaempferi plantations of various stand ages in central Japan to examine and compare the effect of stand age on the abundance, size, and species composition of snags (standing dead trees) compared to those in secondary broadleaf forests. Plantations that were older than the standard rotation age had more and larger snags than young plantations, and the species diversity of snags was positively correlated w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 68 publications
1
9
0
Order By: Relevance
“…Increasingly, snags have been studied in managed forests to determine snag dynamics (Chambers, Mast 2005;Russel, Weiskittel 2012), snag abundance and snag recruitment (Bull et al 1990;Ganey 1999;Harris 1999;Stephens 2004;Moroni, Harris 2010), effects of orography (Gale 2000;Clark et al 2002) and eff ects of shelterwood cut (Kenefic, Nyland 2007). Snag and deadwood size and abundance are highly variable among regions and are dependent on forest type, successional stage, climate and forest management regimes (Fan et al 2003(Fan et al , 2004Böhl, Brändli 2007;Nagaike 2009). Diff erent management regimes aff ect snag richness (Pedlar et al 2002;Ganey, Vojta 2005;Stephens, Moghaddas 2005;Kenefic, Nyland 2007).…”
mentioning
confidence: 99%
“…Increasingly, snags have been studied in managed forests to determine snag dynamics (Chambers, Mast 2005;Russel, Weiskittel 2012), snag abundance and snag recruitment (Bull et al 1990;Ganey 1999;Harris 1999;Stephens 2004;Moroni, Harris 2010), effects of orography (Gale 2000;Clark et al 2002) and eff ects of shelterwood cut (Kenefic, Nyland 2007). Snag and deadwood size and abundance are highly variable among regions and are dependent on forest type, successional stage, climate and forest management regimes (Fan et al 2003(Fan et al , 2004Böhl, Brändli 2007;Nagaike 2009). Diff erent management regimes aff ect snag richness (Pedlar et al 2002;Ganey, Vojta 2005;Stephens, Moghaddas 2005;Kenefic, Nyland 2007).…”
mentioning
confidence: 99%
“…Ramovs and Roberts [45] identified a gradient in cover of foresthabitat species which ranged from being lowest in oldfield plantations, intermediate in cut-over plantations and young, naturally regenerated stands, and highest in mature, naturally regenerated stands. Nagaike [46] showed that the species diversity of snags (standing dead trees), which are an important structural attribute of forest ecosystem diversity [1,47], was positively correlated to stand age in L. kaempferi plantations, supporting the positive correlation between tree species diversity and species richness with stand age [48]. Conversely, in the herb layer of the study plots examined by Nagaike et al [48], plant species diversity was not correlated with stand age, but the attributes of some species (e.g., weed species) were negatively correlated with stand age and the occurrence frequency of species.…”
Section: Studies On Plant Species Diversity and Species Richness In Pmentioning
confidence: 99%
“…The Japanese larch ( Larix kaempferi (Lamb.) Carrière) is an endemic coniferous species in Honshu Island, central Japan [ 2 , 3 , 4 , 5 ], but it is a non-native and key plantation species in Hokkaido, northern Japan [ 6 ]. It is an economically important deciduous conifer species that grows in cool-temperate forests [ 4 ].…”
Section: Introductionmentioning
confidence: 99%